Estimation of the Pore Microstructure of Tight-Gas Sandstone Reservoirs with Seismic Data - Cheng, Wei; Ba, Jing; Carcione, José M.; Pang, Mengqiang; Wu, Chunfang (Frontiers in Earth Science, 2021)
Tight-sandstone reservoirs have a complex pore structure with microcracks and intergranular pores, which have a significant impact on the seismic properties. We have performed ultrasonic measurements at different confining pressures for 15 tight-gas sandstone samples of the Xujiahe formation in Western Sichuan Basin, and have available well-log and seismic data of this area. The aim of this work is to estimate the porosity and crack properties for variable pressure conditions. The EIAS (equivalent inclusion-average stress) model is adopted to compute the high- and low-frequency bulk and shear moduli as a function of crack aspect ratio and (soft) and (stiff) porosities. Then, we use the EIAS-Zener anelastic model to obtain the wave properties as a function of frequency, and compare results with those of the constant Q (Kjartansson) one for verification of the robustness of the approach. The corresponding P-wave impedance, density and phase velocity ratio (VP/VS) are computed in order to built 3D rock‐physics templates (RPTs) at the ultrasonic, well-log and seismic frequency bands. The methodology is applied to a survey line crossing two wells, which together with the laboratory experiments, provide calibration suitable data. The estimated stiff porosity and crack porosity and density are consistent with the available data and actual production records, indicating that 3D RPTs provide a useful interpretation tool in seismic exploration and prospect evaluation.